2021
DOI: 10.4103/amh.amh_49_21
|View full text |Cite
|
Sign up to set email alerts
|

Cyberchondria

Abstract: Background: It is common among medical students to incorrectly believe that they have contracted certain diseases they have recently studied. This belief can be seen in the form of health anxiety and investigating health-related information via the Internet. Cyberchondria denotes repeated online searches for health-related information that are associated with increasing levels of health anxiety. Aims: We aimed to study the prevalence and severity of cyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…22 Another study showed that people with prior diagnoses had somewhat higher cyberchondria severity scores than those who had no prior diagnoses. 23 Similarly, more than half of the participants reported that they searched health-related information to self-diagnose their medical concerns. The findings were consistent with earlier research.…”
Section: Discussionmentioning
confidence: 99%
“…22 Another study showed that people with prior diagnoses had somewhat higher cyberchondria severity scores than those who had no prior diagnoses. 23 Similarly, more than half of the participants reported that they searched health-related information to self-diagnose their medical concerns. The findings were consistent with earlier research.…”
Section: Discussionmentioning
confidence: 99%